Proceedings of the 2018 International Symposium on Physical Design 2018
DOI: 10.1145/3177540.3178243
|View full text |Cite
|
Sign up to set email alerts
|

Standard CAD Tool-Based Method for Simulation of Laser-Induced Faults in Large-Scale Circuits

Abstract: Designing secure integrated systems requires methods and tools dedicated to simulating -at early design stages-the effects of laserinduced transient faults maliciously injected by attackers. Existing methods for simulation of laser-induced transient faults do not take into account IR drop effects that are able to cause timing failures, abnormal reset, and sram flipping. This paper proposes a novel standard cad tool-based method allowing to simulate laser-induced faults in large-scale circuits. Thanks to a powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Laser fault injection attacks rely on parasitic currents generated by laser shots [21] that produce undesired transient voltage, propagating through the logic which can potentially invert bits at the inputs of registers [40]. In Table 1, we outline the characteristics of the three basic levels of laser fault injection attack simulation techniques.…”
Section: Motivationmentioning
confidence: 99%
See 3 more Smart Citations
“…Laser fault injection attacks rely on parasitic currents generated by laser shots [21] that produce undesired transient voltage, propagating through the logic which can potentially invert bits at the inputs of registers [40]. In Table 1, we outline the characteristics of the three basic levels of laser fault injection attack simulation techniques.…”
Section: Motivationmentioning
confidence: 99%
“…The time duration for the AES and deep learning attack by Breier et al, and AES attack by Giraud et al is the simulation time needed to get the results shown in Figure 4, Figure 6 and Figure 5 respectively. A previous work [40] proposes the state-of-the-art layout-based laser fault simulation that models faults injected by a laser at electrical level, which is at a lower level than logical level used in this work, and simulates non afected cells with gate level accuracy. Modelling laser faults at a lower level of abstraction is an alternative way to get a more realistic result, but takes a lot longer to simulate.…”
Section: Laser Fault Injection Attacksmentioning
confidence: 99%
See 2 more Smart Citations